Prognostic Analysis of Duodenal Gastrointestinal Stromal Tumors - Liwen Hong; Tianyu Zhang; Yun Lin; Rong Fan; Maochen Zhang; Mengmeng Cheng; Xiaolin Zhou; Juntao Sun; Peijun Sun; Qiangqiang Wu; Lei Wang; Zhengting Wang; et al. (Gastroenterology Research and Practice)
Aim. This study aims to analyze factors possibly related to the prognosis of duodenal gastrointestinal stromal tumors (DGISTs). Methods. We collected and retrospectively analyzed clinical and pathological data of 62 patients with primary DGISTs. All the patients were hospitalized and received complete surgical resection at Shanghai Ruijin Hospital from September 2003 to April 2015. We followed up the patients to determine survival outcomes. We also analyzed the effect of clinical and pathological factors on disease-free survival (DFS) and overall survival (OS) of the patients. Results. Kaplan-Meier univariate survival analysis demonstrated that tumor size, mitotic index, Ki-67 index, and pathological risk were correlated with the DFS and OS of the patients (DFS P=0.039, 0.001, <0.001, and 0.005, resp.; OS P=0.027, 0.007, <0.001, and 0.012, resp.). Cox multivariate regression analysis revealed that Ki-67 index was an independent prognostic factor affecting DFS and OS (P=0.007 and 0.028, resp.). Moreover, Kaplan-Meier survival analysis showed that imatinib treatment for patients with recurrence was correlated with prolonged OS (P=0.002). Conclusion. Prognosis for DGIST treated by R0 resection is favorable. High level of Ki-67 can be an independent risk factor of DGIST prognosis. Adjuvant imatinib therapy for patients with tumor recurrence could probably lead to prolonged survival.